The Role of NF-kB in the Downregulation of Organic Cation Transporter 2 Expression and Renal Cation Secretion in Kidney Disease - Han, Chao; Zheng, Juan; Wang, Fengyi; Lu, Qingyang; Chen, Qingfa; Hu, Ankang; Visentin, Michele; Kullak-Ublick, Gerd A.; Gai, Zhibo; Chu, Lei (Frontiers in Medicine, 2022)
Organic cation transporter 2 (OCT2), encoded by the SLC22A2 gene, is the main cation transporter on the basolateral membrane of proximal tubular cells. OCT2 facilitates the entry step of the vectorial transport of most cations from the peritubular space into the urine. OCT2 downregulation in kidney disease models is apparent, yet not clear from a mechanistic vantage point. The aim of this study was to explore the role of inflammation, a common thread in kidney disease, and NF-kB in OCT2 modulation and tubular secretion. Among the OCTs, OCT2 was found consistently downregulated in the kidney of rats with chronic kidney disease (CKD) or acute kidney injury (AKI) and in patients diagnosed with CKD, and it was associated with the upregulation of TNFα renal expression. Exposure to TNFα reduced the expression and function of OCT2 in primary renal proximal tubule epithelial cells (RPTEC). Silencing or pharmacological inhibition of NF-kB rescued the expression of OCT2 in the presence of TNFα, indicating that OCT2 repression was NF-kB-dependent. In silico prediction coupled to gene reporter assay demonstrated the presence of at least one functional NF-kB cis-element upstream the transcription starting site of the SLC22A2 gene. Acute inflammation triggered by lipopolysaccharide injection induced TNFα expression and the downregulation of OCT2 in rat kidney. The inflammation did reduce the active secretion of the cation Rhodamine 123, with no impairment of the glomerular filtration. In conclusion, the NF-kB pathway plays a major role in the transcriptional regulation of OCT2 and, in turn, in the overall renal secretory capacity.